Cortical Response and Functional Connectivity in Patients With Subacute Stroke During Dual Task: An fNIRS Study. - Liu, Wu; Huo, Congcong; Zhang, Simin; Zhang, Xuemin; Shao, Guangjian; Chen, Tiandi; Liu, Jizhong; Li, Zengyong (Archives of Physical Medicine & Rehabilitation, 2026)
To investigate neural plasticity changes in patients with subacute stroke during single motor task and dual-task execution. Case-control study. Rehabilitation department in a single hospital. Twenty patients with subacute stroke (mean age, 63.8±10.4y; Mini-Mental State Examination score >20) and 20 age- and sex-matched healthy controls (mean age, 60.95±9.5y) recruited via convenience sampling. Not applicable. A functional near-infrared spectroscopy (fNIRS) system was used to evaluate hemodynamic responses in prefrontal, motor, and occipital regions during single motor task and motor-cognitive dual-task conditions, and functional connectivity (FC) was calculated for each task state. Healthy controls showed widespread activation increases during dual-task versus single motor task (P <.05), whereas patients with stroke exhibited enhanced activation only in ipsilesional prefrontal cortex (P =.041) and contralesional supplementary motor area (P =.045). Controls demonstrated significantly higher sensorimotor activation than patients with stroke during dual-task (P =.001). FC analysis revealed increased prefrontal-premotor connectivity in controls (P =.027), whereas patients with stroke showed enhanced bilateral prefrontal (P =.032), premotor (P =.034), and occipital (P =.043) connectivity. In patients with stroke, premotor area activation is negatively correlated with pace (ρ=−0.53, P =.025), heel-strike angle (ρ=−0.73, P =.029), and swing phase (ρ=−0.56, P =.015), but positively with support phase (ρ=0.56, P =.015). This study confirms that motor-cognitive dual task paradigms effectively induce activation in the ipsilesional cortex of patients with stroke while enhancing interhemispheric FC, demonstrating significant neuromodulatory effects of dual-task training in stroke rehabilitation; simultaneously, it validates the feasibility of utilizing fNIRS combined with motor paradigms for real-time assessment of neuroplasticity changes.